Firms, crowds, and innovation. (May 2017) - Felin, Teppo; Lakhani, Karim R; Tushman, Michael L
The purpose of this article is to suggest a (preliminary) taxonomy and research agenda for the topic of "firms, crowds, and innovation" and to provide an introduction to the associated special issue. We specifically discuss how various crowd-related phenomena and practices—for example, crowdsourcing, crowdfunding, user innovation, and peer production—relate to theories of the firm, with particular attention on "sociality" in firms and markets. We first briefly review extant theories of the firm and then discuss three theoretical aspects of sociality related to crowds in the context of strategy, organizations, and innovation: (1) the functions of sociality (sociality as extension of rationality, sociality as sensing and signaling, sociality as matching and identity), (2) the forms of sociality (independent/aggregate and interacting/emergent forms of sociality), and (3) the failures of sociality (misattribution and misapplication). We conclude with an outline of future research directions and introduce the special issue papers and essays.